Comparative study on the in vitro effects of Pseudomonas aeruginosa and seaweed alginates on human gut microbiota. - Shaofeng Bai; Huahai Chen; Liying Zhu; Wei Liu; Hongwei D Yu; Xin Wang; Yeshi Yin (PLoS ONE)
Alginates pertain to organic polysaccharides that have been extensively used in food- and medicine-related industries. The present study obtained alginates from an alginate overproducing Pseudomonas aeruginosa PAO1 mutant by screening transposon mutagenesis libraries. The interaction between bacterial and seaweed alginates and gut microbiota were further studied by using an in vitro batch fermentation system. Thin-layer chromatography (TLC) analysis indicated that both bacterial and seaweed alginates can be completely degraded by fecal bacteria isolated from study volunteers, indicating that a minor structural difference between bacterial and seaweed alginates (O-acetylation and lack of G-G blocks) didn't affect the digestion of alginates by human microbiota. Although, the digestion of bacterial and seaweed alginates was attributed to different Bacteroides xylanisolvens strains, they harbored similar alginate lyase genes. Genus Bacteroides with alginate-degrading capability were enriched in growth medium containing bacterial or seaweed alginates after in vitro fermentation. Short-chain fatty acid (SCFA) production in both bacterial and seaweed alginates was also comparable, but was significantly higher than the same medium using starch. In summary, the present study has isolated an alginate-overproducing P. aeruginosa mutant strain. Both seaweed and bacterial alginates were degraded by human gut microbiota, and their regulatory function on gut microbiota was similar.